Consumer Expectations of Russian Population (1996−2009): How are Cohort, Generation and Age Related? - Ibragimova, Dilyara (Journal of Economic Sociology, 2014)
The research deals with the analysis of consumer expectations of Russian population, which are mediated by many socio-demographic characteristics: income, age, education, place of residence, sex, etc. The paper points up the influence on variable “age” because it is rather complex itself. First, actual age represents biological characteristics. Second, “age” represents a unique birth cohort in terms of socialization and formation of life experience. Finally, all ages feature influence by a time period effect that reflects the socio-political, economic, and informational phenomena of the macro environment. Solving the problem of “identification” (i. e. the separation of these three effects), which inevitably arises in case of cohort analysis, is based on theoretical views concerning the character of consumer expectations and the results of empirical testing. Its point is that the aggregated Consumer Sentiment Index (CSI) reflects the general socio-economic situation in a country at a certain time and allows us to use the CSI as a distillation of a specific time moment. The information base of research is the data of consumer survey although not the panel, but conducted over a 15-year period on the same methodology and sample. All 79 waves of cross-section data (from May 1996 to September 2009) were converted into a “quasi-longitudinal design”, the total sample of dataset was 182,507 respondents. The regression analysis demonstrates that belonging to a cohort actually determines significantly consumer sentiments. However, the nonlinear correlation describing such dependence showed that an increase of optimism/pessimism in respect for the economic and social development of the country happens non-uniformly from one cohort to another. In addition, the article attempts to implement approach to differentiation of generations, is not based on age differences, and the relationship with historical events. The research shows that an indicator such as the CSI could be one instrument for defining the time boundaries of the generations.